A pilot study to promote walking among obese and overweight individuals: walking buses for adults. Issue 6 (June 2015) - Baker, E.H.; Milner, A.N.; Campbell, A.D.
Highlights Walking buses have been successfully used for transporting young children Walking buses increase physical activity (PA) and promote improved outcomes for children We designed a PA intervention to promote walking among obese/overweight adults We find that walking buses promote PA and weight loss among the walking bus users Weight loss was even more pronounced for black participants